Pengaruh Biaya Iklan dan Biaya Penjualan Personal Terhadap Nilai Penjualan pada PT. Telekomunikasi Indonesia, Tbk. - Chairul Anwar; . Rinna (Universitas Bandar Lampung (UBL), 2015)
This research aims to examine the influence of advertising costs and personal selling costs onsales values PT. Telekomunikasi Indonesia, Tbk., period 2006-2012. The first hypothesis in this research is advertising costs influential on sales values PT. Telekomunikasi Indonesia, Tbk. The second hypothesis in this research is personal selling costs influential on sales values PT. Telekomunikasi Indonesia, Tbk. The third hypothesis in this research is advertising costs and personal selling costs influential simultaneous on sales values PT. Telekomunikasi Indonesia, Tbk. Advertising costs gives the bulk approach to public, while personal selling costs gives personal approach by face to face with consumen. The data used in this research is the quantity data as the secondary is financial report PT. Telekomunikasi Indonesia, Tbk., there is in the Indonesia Stock Exchange period 7 years (2006-2012). The technique of data analysis in this research is multiple linier regression and the hypothesis test with t test using SPSS 18.0 for windows. The results research showed that (1) Advertising costs influential on sales values PT. Telekomunikasi Indonesia, Tbk. (2) Personal Selling costs influential on sales values PT. Telekomunikasi Indonesia, Tbk. (3) Advertising costs and personal selling costs influential simultaneous on sales values PT. Telekomunikasi Indonesia, Tbk. Variable advertising costs and personal selling costs give big contribution for the increase sales values PT. Telekomunikasi Indonesia, Tbk.